The effectiveness of The Malaysia Anti Corruption Commission Act 2008: a study on compliance with the Malaysian Anti Corruption Committee / Aimi Adibah Mohd Zahir … [et al.] - Mohd Zahir, Aimi Adibah; Ali, Aziah; Embong, Raihana; Ali, Siti Nur Afifah (2010)
The title of this research is "The Effectiveness of the Malaysian Anti Corruption Commission Act 2008: A Study on Compliance with the Malaysian Anti Corruption Committee". This research is conducted to identify the compliance of Malaysian Anti Corruption Committee with the Act. The current situation in Malaysia relating to the issue of corruption is not really serious but certain measurements were made in order to control this issue before getting worse. Basically, there many causes that contributes to the existence of corruption in Malaysia. As for that, as the citizen of Malaysia, there is a need to find solutions in solving or combating corruption. Although, there is law that governs this issue, still these problems occur among the society. Furthermore, at the end of the research, we will come out with few suggestions for the Malaysian Anti Corruption Committee to strengthen their regulation in settling this issue of corruption. We hope that through the recommendation Malaysian Anti Corruption Committee will improve in their service.